2019
DOI: 10.3892/ol.2019.11029
|View full text |Cite
|
Sign up to set email alerts
|

miR‑331‑3p suppresses cell invasion and migration in colorectal carcinoma by directly targeting NRP2

Abstract: Colorectal carcinoma (CRC) is a common tumor of the digestive system with poor prognosis. Studies have shown that aberrant microRNA (miRNA) expression can affect CRC progression by regulating target genes. In the present study, we investigated the functional roles and potential mechanisms of miR-331-3p in CRC. The expression of miR-331-3p and neuropilin-2 (NRP2) in CRC was detected by RT-qPCR. Then, Transwell assays were conducted to investigate the influence of miR-331-3p on CRC cell invasion and migration ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
2
18
0
2
Order By: Relevance
“…CRC is a fatal illness with high mortality and morbidity (35), and high rates of metastasis and recurrence (6). Despite the use of surgical and adjuvant therapy, the survival rate has not improved dramatically, and ~50% of patients die from local recurrence or metastasis following surgery (36). Novel biomarkers and effective therapeutic targets are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is a fatal illness with high mortality and morbidity (35), and high rates of metastasis and recurrence (6). Despite the use of surgical and adjuvant therapy, the survival rate has not improved dramatically, and ~50% of patients die from local recurrence or metastasis following surgery (36). Novel biomarkers and effective therapeutic targets are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MIR-17-5p and MIR-20a are both highly expressed in colon cancer tissues, and the MIR-106 family was also found to be closely involved in the initiation and development of colorectal cancer [ 31 , 32 ]. On the contrary, the miRNA target of IRF7, MIR-331, was reported to be a tumor suppressor in colorectal carcinoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we found miR-331 was a new miRNA which has not been reported in transmission of drug resistance. It has been reported that miR-331-3p could inhibit the proliferation and migration of colon cancer by targeting NRP2 18 .Another study showed that circ-0001649 sponges with miR-331-3p, further to achieve inhibition of miR-331-3p so that the biological process of non-small cell lung cancer was suppressed 19 .The high expression of miR-331-3p in serum was considered to be one of the high risk factors for esophageal cancer recurrence.Studies related to miR-331 and chemotherapy in leukemia have shown that the increased expression of miR-331 may lead to poor e cacy and lower survival rate 20 .The above studies have shown that miR-331-3p can cause tumor recurrence and poor prognosis in some tumors. In conclusion, we found that the regulatory role of miR-331 in different tumors is not uniform.…”
Section: Mir-331 Carried By Exosomes Could Promote the Autophagy To Induce Drug Resistance In Osmentioning
confidence: 99%